Effects of mechanical and thermal load cycling on micro tensile bond strength of clearfil SE bond to superficial dentin - Ali Reza Daneshkazemi; Abdol Rahim Davari; Ebrahim Ataei; Fariba Dastjerdi; Ehsan Hajighasemi (Wolters Kluwer Medknow Publications, 2013)
Background: Certain studies have been conducted on the effects of mechanical and thermal load cycling on the microtensile bond strength (microTBS) of composites to dentin, but the results were different. The authors therefore decided to evaluate these effects on the bonding of Clearfil SE bond to superficial dentin. Materials and Methods: Flat dentinal surface of 42 molar teeth were bonded to Filtek-Z250 resin composite by Clearfil SE bond. The teeth were randomly divided into 7 groups and exposed to different mechanical and thermal load cycling. Thermocycling was at 5-55°C and mechanical load cycling was created with a force of 125 N and 0.5 Hz. Then, the teeth were sectioned and shaped to hour glass form and subjected to microTBS testing at a speed of 0.5 mm/min. The results were statistically analyzed by computer with three-way analysis of variance and T-test at P < 0.05 significant. To evaluate the location and mode of failure, the specimens were observed under the stereomicroscope. Then, one of the specimens in each group was evaluated under Scanning Electron Microscopy (SEM) for mode of failure. Results: All of the study groups had a significantly lower microTBS as compared to the control group ( P < 0.001). There was no statistically significant difference between mechanical cycling with 50K (kilo = 1000) cycles, and 50K mechanical cycles plus 1K thermal cycles. Most of the fractures in the control group were of adhesive type and this type of fracture increased after exposure to mechanical and thermal load cycling. Conclusion: Thermal and mechanical load cycling had significant negative effects on microTBS and the significant effects of mechanical load cycling started to be significant at 100K cycles.